MEWUJUDKAN DESA WISATA MELALUI PENGEMBANGAN POTENSI LOKAL PADA DESA PENGALANGAN, KABUPATEN GRESIK - Ermawati, Yuli; Kusuma, Pramandyah Fitah; Aditya, Indah Setyorini (STIE Pelita Nusantara, 2023)
The aim of village development is to build villages so that they have development capacity and independence through village financial independence which is characterized by high capacity of Regional Original Income. Pengalangan Village actually has local potential as an alternative source of income for the village, one of this potential is a park known as Sunflower Park. The limited ability of local communities to develop tourism village programs and the rainy season has damaged the condition of tourist attractions, so efforts are needed to revitalize them. That is why the development of tourist villages requires assistance from stakeholders. The aim of the Lecturer and Student Community Service packaged in the Thematic KKN Program from Wijaya Putra University is to revitalize and restore the potential function of Sunflower Park to become a tourist destination in Pengalangan Village. The assistance provided is revitalizing tourist attractions by repairing tourist attraction machines, making outbound rides, providing assistance in increasing Knowledge Skills or technical managerial abilities for tourism managers, and forming tourism awareness groups involving BUMDes, Village Level Karang Taruna, and MSME actors in Pengalamgan Village.